Aristotle’s Theory on the Mixed Spartan Regime and the Athenian Father-State - Krikona, Eleni (Conatus - Journal of Philosophy, 2018)
Aristotle shifts the criteria for characterizing the nature of a regime from those that determine the political status of a city (criteria for inclusion in the political body and city authorities) into the nature of the institutions and the balancing of the political powers of the heterogeneous parts of a city. This leads to two new types of "mixed" Democracy, which are widely presented to converge, and, as I will claim in this paper, are not essentially different from moderate oligarchy.